Studies on the Solid Phase Extraction and Spectrophotometric Determination of Palladium with 2-(2-Quinolylazo)- 5-Dimethylaminoaniline as Chromogenic Reagent - LIN, HAITAO; LIYA, ZHU; HUANG, ZHANGJIE; HU, QIUFEN; ZHANG, GAN; YANG, GUANGYU (Asian Journal of Chemistry, 2010)
A sensitive, selective and rapid method for the determination of palladium with 2-(2-quinolylazo)-5-dimethylaminoaniline (QADMAA) as chromogenic reagent and the solid phase extraction of the Pd(II)-QADMAA chelate with a reversed phase polymer-based C18 cartridge was developed. In the presence of 0.05-0.5 mol/L of hydrochloric acid solution and cetyl trimethylammonium bromide (CTMAB), QADMAA reacts with palladium(II) to form a violet complex of a molar ratio 1:2. This chelate was enriched by the solid phase extraction with a polymer-based C18 cartridge. The enrichment factor of 200 was obtained by elution of the chelates from the cartridge with minimal amount of isopentyl alcohol. In the isopentyl alcohol medium, the molar absorptivity of the chelate is 1.41 × 105 L mol-1 cm-1 at 618 nm. Beer’s law is obeyed in the range of 0.01-1.2 μg/mL. The relative standard deviation for eleven replicate sample of 0.2 μg/L level is 2.05 %. The detection limit reaches 0.02 μg/L in the original samples. This method had been applied to the determination of palladium in environmental samples with good precision.